2012
DOI: 10.3109/0142159x.2012.689442
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of two different types of web-based instructional methods: One with case-based scenarios and one without

Abstract: Background: Computer-based learning (CBL) is an effective form of medical education. Educators have developed recommendations for instructional design but there is only minimal research that evaluates these recommendations. Aim: To evaluate the effect of case-based questions contained in computer modules on learning efficacy. Methods: The authors conducted a randomized controlled trial in 124 medical students of two CBL PowerPoint modules-based on Medicare. The modules were identical except one contained 11 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…And although there is evidence for the use of this educational model, this evidence has not linked casebased learning specifically to clinical reasoning in occupational therapy in the past (Boyt Schell & Schell, 2008;Falk-Kessler & Ciaravino, 2006;Lederer, 2007;Mattingly, 1991;Rogers, 1983;Unsworth & Baker, 2016;Vogel et al, 2009). Although case-based learning outcomes have included student engagement, knowledge acquisition, and higher course grades (Kaddoura, 2011;Mounsey & Reid, 2012;Thistlethwaite et al, 2012), this study provides a more vital link to the inductive reasoning skills necessary for effective clinical reasoning and to address the complexities of the provision of individualized services to individuals.…”
Section: Implications For Occupational Therapy Education and Further mentioning
confidence: 99%
See 2 more Smart Citations
“…And although there is evidence for the use of this educational model, this evidence has not linked casebased learning specifically to clinical reasoning in occupational therapy in the past (Boyt Schell & Schell, 2008;Falk-Kessler & Ciaravino, 2006;Lederer, 2007;Mattingly, 1991;Rogers, 1983;Unsworth & Baker, 2016;Vogel et al, 2009). Although case-based learning outcomes have included student engagement, knowledge acquisition, and higher course grades (Kaddoura, 2011;Mounsey & Reid, 2012;Thistlethwaite et al, 2012), this study provides a more vital link to the inductive reasoning skills necessary for effective clinical reasoning and to address the complexities of the provision of individualized services to individuals.…”
Section: Implications For Occupational Therapy Education and Further mentioning
confidence: 99%
“…Learning outcomes, including increased student engagement in learning, knowledge acquisition, short-term learning, improved critical thinking, and higher course grades, have been documented through case-based instructional methods in a variety of disciplines (Kaddoura, 2011;Mounsey & Reid, 2012;Thistlethwaite et al, 2012). However, there is great variety in how these learning outcomes have been measured in the research process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 Another study evaluating the efficacy of case-based computer modules did find improvements in short-term knowledge, but the improvement was not maintained longterm. 12 In pharmacy education, Romero and colleagues reported enhanced student learning in a pharmaceutics course that used case-based learning, but the observation was based on a positive correlation between case study grades and course examination scores. 21 Brown and colleagues found that students who completed a case-based toxicology elective course performed better on the toxicology subsection of the Pharmacy Curriculum Outcomes Assessment examination than …”
Section: Discussionmentioning
confidence: 99%
“…Strong objective evidence is lacking. [10][11][12][13][14][15][16] At the Feik School of Pharmacy, Applied Pharmacy Care is a series of 6 courses that focuses on the application of pharmaceutical care principles, pharmaceutical knowledge, and professional techniques to solve patient-and medication-related issues. 17 Health literacy had been taught in only 1 course, Applied Pharmacy Care II, to first-year (P1) pharmacy students.…”
Section: Introductionmentioning
confidence: 99%